Burden of seasonal influenza in sub-Saharan Africa: a systematic review protocol. Issue 10 (10th October 2018) - Sambala, Evanson Zondani; Mdolo, Aaron; Banda, Richard; Phiri, Arthur; Wiyeh, Alison B; Wiysonge, Charles Shey
Abstract : Introduction: Measures of epidemiological burdens are an important contribution to estimating disease severity and determining the at-risk populations for seasonal influenza. In the absence of these data, it is extremely difficult for policy-makers to decide on how to distribute limited resources. This systematic review will synthesise the literature on reported burden of seasonal influenza (eg, morbidity and mortality) in sub-Saharan Africa. Method and analysis: We will include published epidemiological studies that capture the burden estimation of seasonal influenza between 1 January 2000 and 31 August 2018. Studies that have reported disease burden estimates associated to influenza-like illness, acute respiratory illness, acute lower respiratory illness, severe acute respiratory illness and severe or very severe pneumonia using laboratory-confirmed influenza cases will be included. We will perform a multiple electronic database search in PubMed, Embase, African Journals Online, Cochrane, Web of science, CINAHL and Google scholar for eligible studies. The reference lists of relevant studies will also be hand-searched for potentially eligible studies. The titles and abstracts of identified records will be screened independently by two authors. The full-text articles of potentially eligible studies will be assessed independently by two authors. Discrepancies will be resolved by discussion, and by a third author if the first two authors fail to come to a consensus. The measures of the burden of influenza will be aggregated using a meta-analysis for homogeneous studies and narrative synthesis if the studies are heterogeneous. The strength of the evidence will be assessed using the Grading of Recommendations Assessment, Development and Evaluation approach. Ethics and dissemination: This systematic review will use publicly available data; and as such, no formal ethical review is required. Our findings will be published in a peer-reviewed journal and also disseminated through conferences and stakeholder meetings. PROSPERO registration number: CRD42017074091.